Multiphysics Simulation of Blood Flow in Heart with Ventricular Septal Defect - Ahmad Fikri Azfar, Ahmad Azaharia; Mohd Akramin, Mohd Romlay; Mohd Jamil, Mohamed Mokhtarudin; Azam, Ahmad Bakir (Springer, 2024)
Ventricular septal defect (VSD) is the presence of a hole in the septum connecting both left and right ventricles of the heart, which allows the blood to flow in between them. VSD usually occurs in infants, and many will spontaneously close as they age. Therefore, the purpose of this study is to investigate the effect of VSD presence in a biventricular model using Multiphysics simulation involving myocardium mechanics, blood flow, and electrophysiology. Idealized biventricular geometry is used and a VSD of 6 mm diameter is introduced in the septum. In this study, the Multiphysics simulations of a normal heart and a VSD heart have been performed, involving the ventricular wall mechanics, blood flow, and electrophysiology. It is found that for the normal heart, the left ventricular pressure and volume are slightly higher, while the right ventricular pressure and volume are slightly lower than the VSD heart. This is due to the increased amount of blood flowing into the right ventricle chamber in VSD heart from the left ventricle. Further investigation using bigger diameter and location of VSD could uncover more understanding on the differences.